1994
DOI: 10.1128/mcb.14.7.4522
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 is a glucose-regulated transcription factor whose leucine-rich repeat binds several proteins important for placing CCR4 in its proper promoter context.

Abstract: The yeast CCR4 protein is required for the expression of a number of genes involved in nonfermentative growth, including glucose-repressible ADH2, and is the only known suppressor of mutations in the SPT6 and SPT10 genes, two genes which are believed to be involved in chromatin maintenance. We show here that although CCR4 did not bind DNA under the conditions tested, it was able to activate transcription when fused to a heterologous DNA-binding domain. The transcriptional activation ability of CCR4, in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
128
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 45 publications
3
128
0
Order By: Relevance
“…40, and is therefore involved in auto-immune reactions in the aging mice. It could also encode a factor involved in transcriptional regulations: actually, the CCR4 protein is a transcription factor for the glucose-repressible genes in yeast (41), and recently Draper et al (42) identified a mouse protein that binds to the yeast CCR4 protein, resulting in a protein complex with evolutionarily conserved transcriptional functions. The presently identified ORF could be an exon of the mouse homologue (which still remains to be characterized) of the yeast CCR4 gene, and the IAP sequence be inserted within an intron of the corresponding gene.…”
Section: An Evolutionarily Conserved Orf With Similarity To the Yeastmentioning
confidence: 99%
“…40, and is therefore involved in auto-immune reactions in the aging mice. It could also encode a factor involved in transcriptional regulations: actually, the CCR4 protein is a transcription factor for the glucose-repressible genes in yeast (41), and recently Draper et al (42) identified a mouse protein that binds to the yeast CCR4 protein, resulting in a protein complex with evolutionarily conserved transcriptional functions. The presently identified ORF could be an exon of the mouse homologue (which still remains to be characterized) of the yeast CCR4 gene, and the IAP sequence be inserted within an intron of the corresponding gene.…”
Section: An Evolutionarily Conserved Orf With Similarity To the Yeastmentioning
confidence: 99%
“…2). The Xenopus, murine, and human proteins appear to lack the N-terminal region of yeast CCR4 (from amino acids 1 to 432), which contains a leucine-rich repeat region (amino acids 350 -467) and two activation domains (6). Yet, they display a significant similarity (close to 30%, including conservative amino acid changes) with the yeast CCR4 protein within their C-terminal domains, in a region corresponding to the second and third exons of the Xenopus, murine, and human genes.…”
Section: Murine and Human Yccr4-related Cdnas-a 966-bp Openmentioning
confidence: 99%
“…13 and 15). In this respect, we had previously characterized three IAP transcripts of abnormal size (3,6, and 10 kb, named IAP-AR transcripts), which are induced exclusively in the liver of old mice (16). We have shown that the 10-kb IAP-AR transcript is initiated within the 5Ј-LTR of an * This work was supported by grants from the Association pour la Recherche sur le Cancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations